STRATEGI IMPRESSION MANAGEMENT USTADZ HANAN ATTAKI DALAM AKTIVITAS DAKWAH DI MEDIA SOSIAL - Gustia, Arifah Yenni; Putra, Muhammad Hidayat (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2023)
Ustadz Hanan Attaki is one of the young preachers who can take advantage of developments in technology and communication to broadcast Islam to the younger generation using different characteristics and approaches. With a relaxed and soft speaking style. Ustadz Hanan Attaki built impression management on himself to attract the hearts of the younger generation who were the targets of his preaching. This research aims to determine Ustadz Hanan Attaki's impression management strategy in the form of; (i) stage style (setting), (ii) appearance style, and (iii) behavior style (manner) in preaching via social media. This research uses Erving Goffman's impression management theory with descriptive qualitative methods. The results of the research show that the impression management strategy carried out by Ustadz Hanan Attaki is working well. The use of social media in preaching by conveying light themes that are needed by the younger generation, is the method used by Ustadz Hanan Attaki to get a positive impression. The stylish appearance and relaxed and polite behavior are the main attraction of the younger generation towards the preaching message brought by Ustadz Hanan Attaki.